Lithium-aluminum alloy composite graphite negative electrode material, preparation method thereof, negative electrode plate and lithium ion battery

By using lithium-aluminum alloy composite graphite anode material in lithium-ion batteries and using a carbon layer to coat the lithium-aluminum alloy particles, the problem of low specific capacity and first-term efficiency of graphite anode material in lithium-ion batteries is solved, and higher electrochemical performance and structural stability are achieved.

CN119890251APending Publication Date: 2025-04-25GREE ALTAIRNANO NEW ENERGY INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411834532.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the specific capacity and first-term effect of graphite negative electrode materials are lower, mainly due to the volume expansion and poor surface stability of the material after lithium alloying, resulting in structural powdering and capacity reduction.

Method used

The lithium-aluminum alloy composite graphite negative electrode material is used, which consists of lithium-aluminum alloy particles in the carbon layer coated with graphite core. It is prepared by spray drying and calcining treatment. The thickness of the carbon layer is 50nm to 500nm, and the D50 of the lithium-aluminum alloy particles is 10nm to 150nm.

Benefits of technology

By reducing the volume expansion during lithium alloying, the structural stability of the material is improved, the surface electrochemical stability of lithium-aluminum alloy particles is enhanced, and the specific capacity and first effect of lithium-ion batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186348080000101
    Figure BDA0005186348080000101
  • Figure BDA0005186348080000111
    Figure BDA0005186348080000111
Patent Text Reader

Abstract

The invention provides a lithium-aluminum alloy composite graphite negative electrode material, a preparation method thereof, a negative electrode plate and a lithium ion battery. The lithium-aluminum alloy composite graphite negative electrode material comprises a graphite inner core and a carbon layer coating the outer surface of the graphite inner core, wherein the carbon layer comprises a carbonaceous matrix and lithium-aluminum alloy particles dispersed in the carbonaceous matrix; the thickness of the carbon layer is 50 nm to 500 nm. According to the lithium-aluminum alloy composite graphite negative electrode material provided by the invention, the lithium-aluminum alloy is dispersed in the carbon layer outside the graphite core, so that the volume expansion can be reduced when the obtained material is used as a negative electrode active material of a lithium ion battery and is charged and discharged, and the structural stability of the material is facilitated. Meanwhile, introduction of metal lithium is equivalent to negative electrode pre-lithiation, a lithium source consumed by the SEI membrane can be compensated, the capacity can be provided by the metal lithium, and the specific capacity of the composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a lithium-aluminum alloy composite graphite negative electrode material, a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries are mainly developed in the direction of high energy density. The current commercial graphite negative electrode material has a theoretical specific capacity of 372mAh / g, and can actually reach 355mAh / g, which is close to its theoretical value. If its specific capacity needs to be further improved, it is necessary to improve the structure itself or introduce materials with higher specific capacity. Developing materials with higher specific capacity or introducing materials with higher specific capacity is an effective way to increase the specific capacity of graphite negative electrode materials. At present, the main technical route for introducing higher specific capacity materials to increase the specific capacity of graphite negative electrodes is to introduce silicon-based materials and prepare silicon-carbon materials. The increase in the specific capacity of this composite material is mainly due to the fact that silicon has a theoretical specific capacity of up to 4200mAh / g. However, after being alloyed with lithium, silicon materials will produce huge volume expansion (greater than 300%), resulting in structural pulverization of electrode materials and rapid decrease in capacity, and silicon has poor conductivity. In addition, if the SEI film formed on the silicon surface during charging and discharging is unstable, the SEI film will continue to form, consuming a large amount of active lithium, resulting in low first efficiency and poor cycle performance. Although the stability of silicon-carbon materials has been improved through nano-sizing, carbon coating, pore structure and other methods, this material is generally expensive and difficult to be widely used. The introduction of metal oxides with lithium insertion activity, such as copper oxide, iron oxide, manganese oxide and nickel oxide, can also improve the specific capacity of graphite negative electrode materials. However, this material also has problems of volume expansion and poor surface stability. In addition, the method of increasing the specific capacity of graphite materials by introducing metal oxides also has the problem of inconsistent platforms. The voltage platform of metal oxides is about 1V, while the lithium insertion platform of graphite is about 0.005V.

[0003] Aluminum has the advantages of high theoretical capacity (Li9Al4 can reach 2000mAh / g), good conductivity, and abundant resources. It is one of the ideal choices for negative electrode materials of lithium-ion batteries. After aluminum and lithium are alloyed, its volume changes by about 100%, which is much lower than the volume change of silicon, which is more than 300%. If the amount of lithium reaction can be controlled, the volume expansion can be further reduced, such as Li 0.8 Al has a specific capacity of 793 mAh / g and a volume expansion of only about 75% (Science Advances, 2022, DOI: 10.1126 / sciadv.abn4372). And the cost of aluminum is about 10 times lower than that of silicon.

[0004] However, after aluminum and lithium are alloyed, although the volume expansion is smaller than that of silicon and lithium alloying, the volume expansion problem still needs to be solved. Common methods include amorphization, nano-ization, and carbon composite. Patent CN109671932B disperses nano-aluminum particles in carbon nanofiber materials to alleviate the volume expansion of the Al negative electrode and promote the conductivity of the overall material. However, this method is more complicated and costly. Patent CN202110522809.0 prepares nano-scale metallic aluminum by chemical reaction. The nano-scale size can avoid the pulverization of aluminum during charging and discharging. However, chemical reactions involve many chemical reagents and require higher process conditions, which is not easy to prepare on a large scale. Patent CN202011461244.1 directly uses micron-sized aluminum powder (D50 is 0.5-10μm) and adds a modifier to form hydrogen bonds and chemical bonds on the surface of the aluminum powder. Graphite material is added later to improve the adhesion between aluminum powder and graphite material, and obtain a negative electrode material with high specific capacity and good cycle performance. However, the aluminum powder of this material is not coated with carbon, and the aluminum powder and graphite are only mixed by mechanical mixing, without strong contact between the interfaces, which will affect the conductive properties of the material. In addition, the use of micron-sized aluminum powder still has the potential problem of material pulverization during the subsequent continuous charging and discharging process.

[0005] In addition, similar to silicon materials, the volume changes of metallic aluminum during the charge and discharge process will lead to poor surface stability, which will cause capacity attenuation and fail to achieve the purpose of increasing specific capacity. Pre-lithiation can solve the problems of low initial efficiency and low specific capacity of the material. The current pre-lithiation technology is mainly used to improve the initial efficiency of silicon-based negative electrode materials and the energy density of the whole battery. In terms of negative electrode pre-lithiation, the methods used mainly include direct rolling of metal lithium foil, adding pre-lithiation additives, electrochemical deposition of lithium, and soaking in organic lithium reagents. After pre-lithiation, these methods generally have not been assembled. Therefore, in subsequent processes, the moisture content of the atmosphere needs to be strictly controlled, and even needs to be carried out under anaerobic conditions. This will increase the cost of battery production and is not highly compatible with existing battery processes.

[0006] Based on this, how to compound aluminum with graphite negative electrode active materials in a more suitable form to improve its electrochemical performance, inhibit the pulverization of aluminum-containing negative electrode materials, and ultimately make the corresponding lithium-ion batteries exhibit higher specific capacity and first efficiency is one of the technical problems that need to be solved in this field. Summary of the invention

[0007] The main purpose of the present invention is to provide a lithium-aluminum alloy composite graphite negative electrode material, a preparation method thereof, a negative electrode plate and a lithium-ion battery, so as to solve the problems of low specific capacity and low initial efficiency of lithium-ion batteries in the prior art.

[0008] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a lithium-aluminum alloy composite graphite negative electrode material, which includes a graphite core and a carbon layer coated on the outer surface of the graphite core, the carbon layer includes a carbonaceous matrix and lithium-aluminum alloy particles dispersed in the carbonaceous matrix; the thickness of the carbon layer is 50nm to 500nm.

[0009] Furthermore, the lithium aluminum alloy particles are Li x Al, wherein x is 0.1 to 0.5, and the D50 of the lithium aluminum particles is 10 nm to 150 nm.

[0010] Furthermore, the D50 of the graphite core is 5 μm to 40 μm, and the graphite core is selected from one or more of natural graphite, flake graphite and artificial graphite.

[0011] Furthermore, the weight ratio of the graphite core, the carbonaceous matrix and the lithium aluminum alloy particles is (30-85): (3-20): (13-60).

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned lithium-aluminum alloy composite graphite negative electrode material, comprising: step S1, mixing an aluminum source with a first dispersant, and sequentially performing pre-dispersion and a first ball milling to obtain a first slurry; step S2, adding a lithium source, a graphite core and a carbon source to the first slurry, and obtaining a second slurry by a second ball milling; step S3, sequentially drying and calcining the second slurry to obtain a lithium-aluminum alloy composite graphite negative electrode material.

[0013] Furthermore, in step S1, the stirring speed of the pre-dispersion is 20 Hz to 50 Hz, and the time is 10 min to 120 min; the speed of the first ball mill is 500 r / min to 2500 r / min, and the time is 4 h to 48 h.

[0014] Furthermore, in step S2, the rotation speed of the second ball mill is 2000 r / min to 6000 r / min, and the time is 1 h to 8 h.

[0015] Furthermore, in step S3, the drying is spray drying, and the inlet temperature of the spray drying is 200°C to 400°C, and the outlet temperature is 80°C to 100°C; the calcination temperature is 600°C to 700°C, and the time is 2h to 20h.

[0016] Further, the D50 of the aluminum source is 0.5 μm to 40 μm; preferably, the aluminum source is selected from one or more of aluminum oxide, aluminum hydroxide and boehmite.

[0017] Further, the carbon source is selected from one or more of citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid, carboxymethyl cellulose, polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine formaldehyde resin, epoxy resin, unsaturated polyester resin, polyurethane and polyethylene glycol; and / or, the lithium source is selected from one or more of lithium oxalate, lithium nitrate, lithium carbonate, lithium acetate and lithium hydroxide monohydrate; and / or, the dispersant is selected from one or more of N,N-dimethylformamide, N-methylpyrrolidone, isopropanol, acetonitrile, water, ethanol, acetone, toluene, xylene, chloroform, acetic acid, tetrahydrofuran and dimethyl sulfoxide.

[0018] The third aspect of the present invention provides a negative electrode plate, which includes the above-mentioned lithium aluminum alloy composite graphite negative electrode material.

[0019] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the negative electrode plate is the above-mentioned negative electrode plate.

[0020] By applying the technical solution of the present invention, a lithium aluminum alloy composite graphite negative electrode material is provided, wherein the lithium aluminum alloy is dispersed in the carbon layer outside the graphite core, which can reduce the volume expansion when the obtained material is used as the negative electrode active material of the lithium ion battery and is charged and discharged, which is beneficial to the structural stability of the material. At the same time, the introduction of metallic lithium is equivalent to the pre-lithiation of the negative electrode, which can compensate for the lithium source consumed by the SEI film, and can provide capacity itself, which is beneficial to the improvement of the specific capacity of the composite material. The carbonaceous matrix in which the lithium aluminum alloy is located can improve the surface electrochemical stability of the lithium aluminum alloy, reduce the amount of SEI film formed, and is beneficial to improve the first effect and specific capacity. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0022] As described in the background technology, the lithium-ion battery in the prior art has the problem of low specific capacity and initial efficiency. In order to solve the above technical problems, the first aspect of the present invention provides a lithium aluminum alloy composite graphite negative electrode material, which includes a graphite core and a carbon layer coated on the outer surface of the graphite core, and the carbon layer includes a carbon matrix and lithium aluminum alloy particles dispersed in the carbon matrix; the thickness of the carbon layer is 50nm to 500nm.

[0023] The lithium aluminum alloy composite graphite negative electrode material provided by the present invention comprises lithium aluminum alloy particles in its structure, and the lithium aluminum alloy is dispersed in the carbon layer outside the graphite core. The alloy particles contain lithium and aluminum elements at the same time, both of which can improve the specific capacity of the obtained negative electrode material, especially the introduction of metallic lithium, which is equivalent to pre-lithiation treatment of the negative electrode, so that the material can be used as a negative electrode active material in the subsequent charging and discharging process of the lithium ion battery to compensate for the lithium source consumed by the SEI film. At the same time, the lithium-containing alloy particles can reduce volume expansion during charging and discharging, thereby maintaining the structural stability of the negative electrode material and improving its electrochemical performance.

[0024] Regarding the carbonaceous matrix in which the lithium-aluminum alloy is located, on the one hand, the carbonaceous matrix can improve the surface electrochemical stability of the lithium-aluminum alloy and reduce the amount of SEI film formed, which is beneficial to improving the initial efficiency and specific capacity; more importantly, it can better adapt to the graphite core as the core, thereby improving the compatibility of lithium-aluminum particles in the graphite material system, and ultimately maintaining the overall structural integrity, consistency and stability of the resulting lithium-aluminum alloy composite graphite negative electrode material.

[0025] Of course, compared with the prior art, in which graphite particles and lithium aluminum alloy particles are directly mixed as negative electrode active materials, or the scheme of using both at the same time in the preparation process of the lithium ion battery system through other physical means, the present invention organically links the lithium aluminum alloy particles and the negative electrode active graphite material through a carbon layer, and obtains an integral lithium aluminum alloy composite graphite negative electrode material structure, which has more superior electrochemical properties and more structural stability, so that when used as a negative electrode active material, it can cooperate with other functional components of the lithium ion battery to exert better electrical properties, especially specific capacity and first efficiency.

[0026] It should be emphasized that in the material system provided by the present invention, the lithium aluminum alloy particles are strictly present in the carbon layer coated on the outer surface of the graphite core, and do not enter the graphite core or have direct contact with the graphite core. This is because the lithium aluminum alloy particles may expand in volume during the charge and discharge process of the lithium ion battery in which they are located. If they are directly compounded in the microstructure of the graphite core, this size expansion will cause the graphite core to rupture and pulverize, thereby reducing the cycle life of the battery. At the same time, when the lithium aluminum alloy particles are in the microstructure of the graphite core, they will hinder the diffusion of lithium ions in the graphite negative electrode material, thereby affecting the charge and discharge rate and capacity of the battery.

[0027] Furthermore, in order to better coordinate the mechanical properties and obtain a lithium aluminum alloy composite graphite negative electrode material with higher electrochemical performance, the thickness of the carbon layer is preferably 90 nm to 350 nm.

[0028] In several preferred embodiments, the lithium aluminum alloy particles are Li xAl, where x is 0.1 to 0.5. For lithium aluminum alloy particles, because Li is the main charge storage element, when the Li content increases, the specific capacity of the lithium aluminum alloy particles themselves may increase. However, when the Li content is too high, the stability of the alloy particles may decrease, especially the dimensional expansion problem may be aggravated, thereby affecting its cycle life. x The inventors have optimized the above scheme through a large number of experiments to balance the electrochemical performance and stability of the alloy particles, and to make it better match the carbonaceous matrix in the carbon layer, and finally improve the electrical performance of the lithium-ion battery in which the obtained material is located. Furthermore, in order to better adapt to the carbon layer and obtain a negative electrode material with better electrochemical performance, the D50 of the lithium aluminum alloy particles is preferably 10nm to 150nm.

[0029] Furthermore, in order to coordinate the size relationship between the graphite core, the carbon layer, and the lithium-aluminum alloy particles in the carbon layer, thereby improving the overall consistency of the structure of the obtained lithium-aluminum alloy composite graphite negative electrode material and making it exhibit better electrochemical performance, the D50 of the graphite core is preferably 5μm to 40μm, and the inventors have preferably selected the graphite core from one or more of natural graphite, flake graphite and artificial graphite through a large number of experiments, thereby obtaining a composite material with higher conductivity and better compatibility with the carbon layer and the lithium-aluminum alloy particles therein, which can more significantly improve the electrical performance of the lithium-ion battery in which it is located.

[0030] In order to better coordinate the matching relationship between the graphite core, the carbon matrix and the lithium-aluminum alloy particles, the inventors have optimized the weight ratio of the graphite core, the carbon matrix and the lithium-aluminum alloy particles to be (30-85): (3-20): (13-60) through a large number of experiments, and obtained a lithium-aluminum alloy composite graphite negative electrode material with better and more stable electrochemical performance under this weight relationship.

[0031] In some more preferred embodiments, the graphite core is an artificial graphite core with a D50 of 18 μm to 20 μm, and the lithium aluminum alloy particles are Li 0.3 Al, the carbon layer thickness is 120nm to 122nm; or, the graphite core is an artificial graphite core with a D50 of 10μm to 12μm, and the lithium aluminum alloy particles are Li 0.22 Al, the carbon layer thickness is 95nm to 96nm; or, the graphite core is an artificial graphite core with a D50 of 5μm to 5.5μm, and the lithium aluminum alloy particles are Li 0.4Al, the carbon layer thickness is 23nm to 25nm. The inventors have optimized the specific type and particle size of the graphite core, the specific type of lithium aluminum alloy particles and the specific thickness of the carbon layer through a large number of experiments, and obtained the above-mentioned specific matching schemes, and thus obtained a lithium aluminum alloy composite graphite negative electrode material with superior electrochemical performance, and the lithium ion battery in which it is located also correspondingly shows higher specific capacity and first efficiency.

[0032] The second aspect of the present invention provides a method for preparing the above-mentioned lithium-aluminum alloy composite graphite negative electrode material, comprising: step S1, mixing an aluminum source with a first dispersant, and sequentially performing pre-dispersion and a first ball milling to obtain a first slurry; step S2, adding a lithium source, a graphite core and a carbon source to the first slurry, and obtaining a second slurry by a second ball milling; step S3, sequentially drying and calcining the second slurry to obtain a lithium-aluminum alloy composite graphite negative electrode material.

[0033] In the above preparation method, the ground aluminum source, lithium source and carbon source are mainly mixed in the liquid phase, and the graphite core matrix is ​​added. After spray drying and carbonization, the carbon source is converted into a carbonaceous matrix in the carbon coating layer, and the aluminum source and lithium source are simultaneously converted into lithium aluminum alloy particles and dispersed in the carbonaceous matrix, and finally a composite graphite material with carbon coating and lithium aluminum dispersed and modified in the carbon layer is obtained. Preferably, the above steps S1, S2 and S3 are all carried out in an environment without contact with air, so as to improve the surface stability of the lithium aluminum alloy particles and ultimately improve the overall electrical properties of the obtained material.

[0034] The preparation method provided by the present invention is compatible with traditional battery manufacturing processes and is more convenient for large-scale application.

[0035] In several typical embodiments, in order to obtain lithium aluminum alloy particles with a more suitable particle size and a more uniform particle size distribution, it is preferred that in step S1, the pre-dispersed stirring speed is 20Hz to 50Hz, the time is 10min to 120min, and the speed of the first ball mill is 500r / min to 2500r / min, and the time is 4h to 48h. Pre-treating the aluminum source under the above conditions can more significantly optimize its particle size characteristics, so that it can be better matched with the lithium source to form alloy particles in the future, and alloy particles with higher conductivity and dimensional stability are obtained. After being compounded with the carbon layer, the graphite core is modified to improve the electrochemical properties of the final composite material.

[0036] Furthermore, in order to improve the dispersion uniformity of each raw material component and obtain a composite material with a more stable structure and better electrical properties, it is preferred that in step S2, the rotation speed of the second ball mill is 2000r / min to 6000r / min, and the time is 1h to 8h.

[0037] In order to obtain lithium aluminum alloy particles with more uncertain crystal forms and coordinate the conductivity and stability of the carbonaceous matrix in the carbon layer, the inventors have optimized the drying and calcining conditions for the final composite material through a large number of experiments, and obtained in several typical embodiments that in step S3, the drying is spray drying, and the inlet temperature of the spray drying is 200℃~400℃, and the outlet temperature is 80℃~100℃; the calcination temperature is 600℃~700℃, and the time is 2h~20h. The second slurry is dried and calcined in sequence under the above conditions, which can make the structure of the lithium aluminum alloy particles more stable, the dispersion in the carbon layer more uniform, and the coating of the carbon layer more complete and uniform, so that the obtained lithium aluminum alloy composite graphite negative electrode material has a more stable structure and better electrochemical performance.

[0038] Furthermore, in order to optimize the particle size of the obtained lithium-aluminum alloy particles, the inventors have optimized the D50 of the aluminum source to be 0.5μm to 40μm after a large number of experiments, thereby providing a precursor with a more suitable particle size and distribution for the lithium-aluminum alloy particles formed in the subsequent experimental process, thereby improving the electrochemical properties of the final lithium-aluminum alloy composite graphite negative electrode material; the aluminum source is preferably selected from one or more of aluminum oxide, aluminum hydroxide and boehmite, so as to better realize the combination of metallic lithium, form lithium-aluminum alloy particles with superior electrochemical properties and stronger dimensional stability, and ultimately improve the electrochemical performance of the composite material in which it is located.

[0039] In several typical embodiments, the inventors have selected one or more of citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid, carboxymethyl cellulose, polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine formaldehyde resin, epoxy resin, unsaturated polyester resin, polyurethane and polyethylene glycol through a large number of experiments; and / or, the lithium source is selected from one or more of lithium oxalate, lithium nitrate, lithium carbonate, lithium acetate and lithium hydroxide monohydrate; and / or, the dispersant is selected from one or more of N,N-dimethylformamide, N-methylpyrrolidone, isopropanol, acetonitrile, water, ethanol, acetone, toluene, xylene, chloroform, acetic acid, tetrahydrofuran and dimethyl sulfoxide. In principle, each raw material component can be selected from the types commonly used in the art, and the above raw material types have higher compatibility, so as to form a lithium aluminum alloy composite graphite negative electrode material with a more stable structure and better electrochemical performance.

[0040] The third aspect of the present invention provides a negative electrode plate, which includes the above-mentioned lithium aluminum alloy composite graphite negative electrode material. Because the obtained lithium aluminum alloy composite graphite negative electrode material has a stable microstructure and exhibits excellent electrochemical properties, the corresponding negative electrode plate also has excellent electrochemical properties and can be well adapted to the lithium ion battery system.

[0041] The fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet. The negative electrode sheet in which the above-mentioned lithium-aluminum alloy composite graphite negative electrode material is located exhibits excellent electrochemical performance. When a lithium-ion battery is further prepared, the overall electrochemical performance of the battery, especially the specific capacity and the first efficiency, are significantly improved.

[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0043] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0044] Example 1

[0045] A lithium aluminum alloy composite graphite negative electrode material:

[0046] 1. Add 510g of aluminum oxide with a D50 of 20μm and 2000g of dispersant deionized water into the pre-dispersion tank for pre-dispersion process, with a stirring speed of 40Hz and a time of 15min. After completion, discharge the material, wash the pre-dispersion tank with 1000g of deionized water, transfer the slurry to the ball mill transfer tank, add 1000g of deionized water to dilute the slurry, perform the first ball milling, with a speed of 1500r / min, ball milling for 15h, take out the slurry, add 2000g of water to wash the equipment, and incorporate it into the slurry to obtain the first slurry, in which the D50 of the solid particles is 30nm.

[0047] 2. Transfer the obtained first slurry to a grinding and dispersion transfer tank, add 1192 g of an artificial graphite matrix with a D50 of 18 μm, and pre-dissolve 2239 g of citric acid as a carbon source and 555 g of lithium hydroxide monohydrate as a lithium source in 4457 g of deionized water to obtain a mixed solution. Mix the mixed solution with the first slurry to obtain a slurry with a solid content of 14%, and then perform a second ball milling at a rotation speed of 3500 r / min for 5 hours to obtain a second slurry.

[0048] 3. The obtained second slurry was transferred to a spray drying feeding tank for spray drying. The inlet and outlet temperatures were 300°C and 95°C, respectively, to obtain 4181g of spray powder. Afterwards, the spray powder was calcined at 650°C for 2 hours in a nitrogen atmosphere. During the calcination process, the carbon precursor citric acid was carbonized and converted into a carbon coating layer. At the same time, alumina was reduced to metallic aluminum, and lithium hydroxide was converted into metallic lithium and formed Li with aluminum. 0.3Al lithium aluminum alloy, and finally obtain lithium aluminum alloy composite graphite negative electrode material with a mass of 1602g.

[0049] In the obtained product, the thickness of the carbon layer is 122nm, the D50 of the lithium aluminum particles is 41nm; the weight ratio of the graphite core, the carbon matrix and the lithium aluminum alloy particles is 65:15:20.

[0050] Example 2

[0051] A lithium aluminum alloy composite graphite negative electrode material:

[0052] 1. Add 349g of boehmite with a D50 of 5.0μm and 2000g of dispersant deionized water into the pre-dispersion tank for pre-dispersion process, with a stirring speed of 50Hz and a time of 60min. After completion, discharge the material, wash the pre-dispersion tank with 2000g of deionized water, transfer the slurry to the ball mill transfer tank, add 1000g of deionized water to dilute the slurry, perform the first ball milling, with a speed of 2000r / min, ball milling for 30h, take out the slurry, add 2000g of water to wash the equipment, and incorporate it into the slurry to obtain the first slurry, in which the D50 of the solid particles is 37nm.

[0053] 2. Transfer the obtained first slurry to a grinding and dispersion transfer tank, add 1105g of an artificial graphite matrix with a D50 of 10μm, and pre-dissolve 896g of a carbon source polyvinylpyrrolidone (PVP) and 321g of a lithium source lithium oxalate in 4633g of deionized water to obtain a mixed solution. Mix the mixed solution with the first slurry to obtain a slurry with a solid content of 12%, and then perform a second ball milling at a speed of 3500r / min for 4h to obtain a second slurry.

[0054] 3. The obtained second slurry was transferred to a spray drying feeding tank for spray drying. The inlet and outlet temperatures were 350°C and 100°C, respectively, to obtain 2483g of spray powder. Afterwards, the spray powder was calcined at 700°C for 2 hours in a nitrogen atmosphere. During the calcination process, the carbon precursor PVP was carbonized and converted into a carbon coating layer. At the same time, boehmite was reduced to metallic aluminum. Lithium oxalate was decomposed into lithium oxide, which was further reduced to metallic lithium and combined with aluminum to form Li 0.22 Al lithium aluminum alloy and coated with a carbon layer to finally obtain a lithium aluminum alloy composite graphite negative electrode material with a mass of 1286g.

[0055] In the obtained product, the thickness of the carbon layer is 96nm, the D50 of the lithium aluminum particles is 43nm; the weight ratio of the graphite core, the carbon matrix and the lithium aluminum alloy particles is 75:11:14.

[0056] Example 3

[0057] A lithium aluminum alloy composite graphite negative electrode material:

[0058] 1. Add 1410g of aluminum hydroxide with a D50 of 2.0μm and 3000g of dispersant acetic acid into the pre-dispersion tank for pre-dispersion process, with a stirring speed of 30Hz and a time of 70min. After completion, discharge the material, clean the pre-dispersion tank with 1000g of acetic acid, transfer the slurry to the ball mill transfer tank, add 3000g of acetic acid to dilute the slurry, perform the first ball milling, with a speed of 1900r / min, ball milling for 30h, take out the slurry, add 1000g of acetic acid to clean the equipment, and incorporate it into the slurry to obtain the first slurry, in which the D50 of the solid particles is 17nm.

[0059] 2. Transfer the obtained first slurry to a grinding and dispersion transfer tank, add 500 g of an artificial graphite matrix with a D50 of 5.5 μm, and pre-dissolve 600 g of a carbon source polystyrene and 2308 g of a lithium source lithium acetate in 4787 g of acetic acid to obtain a mixed solution. Mix the mixed solution with the first slurry to obtain a slurry with a solid content of 13%, and then perform a second ball milling at a rotation speed of 3000 r / min for 5 hours to obtain a second slurry.

[0060] 3. The obtained second slurry was transferred to a spray drying feeding tank for spray drying. The inlet and outlet temperatures were 290°C and 100°C, respectively, to obtain 4230 g of spray powder. Afterwards, the spray powder was calcined at 700°C for 4 hours in a nitrogen atmosphere. During the calcination process, the carbon precursor polystyrene was carbonized and converted into a carbon coating layer. At the same time, aluminum hydroxide was reduced to metallic aluminum. After lithium acetate was converted into lithium oxide, it was further reduced to metallic lithium and combined with aluminum to form Li 0.4 Al lithium aluminum alloy and coated with a carbon layer to finally obtain a lithium aluminum alloy composite graphite negative electrode material with a mass of 1249g.

[0061] In the obtained product, the thickness of the carbon layer is 310nm, the D50 of the lithium aluminum particles is 23nm; the weight ratio of the graphite core, the carbon matrix and the lithium aluminum alloy particles is 35:15:50.

[0062] Example 4

[0063] A lithium aluminum alloy composite graphite negative electrode material:

[0064] The difference between this embodiment and embodiment 1 is that the amount of lithium source added in step 2 is changed so that the lithium aluminum alloy particles formed in step 3 are Li 0.08 Al.

[0065] Example 5

[0066] A lithium aluminum alloy composite graphite negative electrode material:

[0067] The difference between this embodiment and embodiment 1 is that the amount of lithium source added in step 2 is changed so that the lithium aluminum alloy particles formed in step 3 are Li 0.7 Al.

[0068] Example 6

[0069] A lithium aluminum alloy composite graphite negative electrode material:

[0070] The only difference between this embodiment and embodiment 1 is that the D50 of the artificial graphite used in step 2 is changed to 3 μm.

[0071] Example 7

[0072] A lithium aluminum alloy composite graphite negative electrode material:

[0073] The only difference between this embodiment and embodiment 1 is that the D50 of the artificial graphite used in step 2 is changed to 45 μm.

[0074] Example 8

[0075] A lithium aluminum alloy composite graphite negative electrode material:

[0076] The only difference between this embodiment and embodiment 1 is that in step 1, the speed of pre-dispersion is changed to 10 Hz and the time is changed to 150 min; and the speed of the first ball mill is changed to 400 r / min and the time is 56 h.

[0077] Example 9

[0078] A lithium aluminum alloy composite graphite negative electrode material:

[0079] The only difference between this embodiment and embodiment 1 is that in step 1, the speed of pre-dispersion is changed to 60 Hz and the time is changed to 8 min; and the speed of the first ball mill is changed to 3000 r / min and the time is 2 h.

[0080] Example 10

[0081] A lithium aluminum alloy composite graphite negative electrode material:

[0082] The only difference between this embodiment and embodiment 1 is that the aluminum source alumina and the dispersant are only mixed as the first slurry, and the pre-dispersion and the first ball milling in step 1 are not performed.

[0083] Embodiment 11

[0084] A lithium aluminum alloy composite graphite negative electrode material:

[0085] The only difference between this embodiment and embodiment 1 is that the conditions for the second ball milling in step 2 are a rotation speed of 1500 r / min and a time of 10 h.

[0086] Example 12

[0087] A lithium aluminum alloy composite graphite negative electrode material:

[0088] The only difference between this embodiment and embodiment 1 is that the conditions for the second ball milling in step 2 are a rotation speed of 6500 r / min and a time of 0.5 h.

[0089] Embodiment 13

[0090] A lithium aluminum alloy composite graphite negative electrode material:

[0091] The only difference between this embodiment and embodiment 1 is that in step 3, the inlet and outlet temperatures of the spray drying are changed to 180° C. and 120° C. respectively; at the same time, the calcination temperature is changed to 500° C., and the calcination time is changed to 24 h.

[0092] Embodiment 14

[0093] A lithium aluminum alloy composite graphite negative electrode material:

[0094] The only difference between this embodiment and embodiment 1 is that in step 3, the inlet and outlet temperatures of the spray drying are changed to 450° C. and 50° C. respectively; at the same time, the calcination temperature is changed to 800° C., and the calcination time is changed to 1 h.

[0095] Comparative Example 1

[0096] A graphite negative electrode material:

[0097] The only difference between this comparative example and Example 1 is that no carbon source citric acid is added in step 2, and an aluminum oxide-lithium oxide modified graphite composite material without carbon coating is obtained.

[0098] Since no carbon source is added to the obtained material, alumina cannot be converted into metallic aluminum, and the aluminum source does not exert its capacity and becomes an inactive substance, reducing the overall specific capacity of the composite material. The lithium source cannot be converted into metallic lithium, and pre-lithiation is impossible, and the initial efficiency is also significantly reduced.

[0099] Comparative Example 2

[0100] A graphite negative electrode material:

[0101] The only difference between this comparative example and Example 1 is that the amount of citric acid, a carbon source, added in step 2 is changed to 224 g, and a composite graphite negative electrode material with a carbon layer thickness of 18 nm is finally obtained.

[0102] In this comparative example, due to the decrease in the amount of carbon source, the aluminum source cannot be completely reduced to metallic aluminum, nor can the lithium source be completely reduced to metallic lithium, and the carbon layer coating amount basically drops to 0, making it difficult to effectively protect the lithium aluminum metal surface. At the same time, the amount of lithium aluminum alloy formed decreases, and the capacity is reduced.

[0103] Comparative Example 3

[0104] A graphite negative electrode material:

[0105] The only difference between this comparative example and Example 1 is that the amount of citric acid, a carbon source, added in step 2 is changed to 900 g, and a composite graphite negative electrode material with a carbon layer thickness of 920 nm is finally obtained.

[0106] In this comparative example, due to the excessive amount of carbon source, the thickness of the formed carbon layer is too large, which leads to slow lithium ion diffusion rate and insufficient capacity. Excessive carbon source reduces the proportion of active materials and also leads to a decrease in overall specific capacity.

[0107] Comparative Example 4

[0108] A graphite negative electrode material:

[0109] The only difference between this comparative example and Example 1 is that lithium oxalate, a lithium source, is not added in step 2.

[0110] Since no lithium source is added, there is no metallic lithium in the obtained composite material, and no lithium-aluminum alloy is formed, and there is no pre-lithiation effect, resulting in a decrease in the specific capacity of the corresponding lithium-ion battery and a decrease in the initial efficiency.

[0111] Comparative Example 5

[0112] A graphite negative electrode material:

[0113] The only difference between this comparative example and comparative example 4 is that after obtaining the composite material in comparative example 4, it is physically blended with lithium aluminum alloy powder at a weight ratio of 4:1 and then used as the negative electrode active material.

[0114] The materials obtained from the above embodiments and comparative examples were used as negative electrode active materials to prepare button half-cells as lithium-ion battery samples, and their gram capacity and first efficiency were tested within the charge and discharge voltage range of 0.005 to 2.0 V. The results are shown in Table 1.

[0115] Table 1

[0116]

[0117]

[0118] From the above description, it can be seen that the above-mentioned embodiments of the present invention realize the preparation of lithium-aluminum alloy composite graphite negative electrode materials with stable structure and excellent electrochemical properties. When it is used as a negative electrode active material in a lithium-ion battery, the prepared lithium-ion battery exhibits high gram capacity and first efficiency.

[0119] Specifically, by comparing the embodiments with the comparative examples, it can be seen that in the case of metallic lithium without carbon coating, too little carbon coating, or without pre-lithiation, the first efficiency and specific capacity of the material after charge and discharge are significantly reduced compared with the corresponding composite material. This is because the introduction of metallic lithium is equivalent to pre-lithiation of the negative electrode, which compensates for the lithium source consumed by the SEI film, and at the same time can provide capacity itself, which is beneficial to the improvement of the specific capacity of the composite material. The presence of carbon coating on the surface of lithium aluminum alloy can improve the surface electrochemical stability of lithium aluminum alloy, reduce the amount of SEI film formed, and is beneficial to improve the first efficiency and specific capacity.

[0120] In addition, by comparing the experimental conditions of each embodiment, it can be seen that if the size of the graphite matrix is ​​too small, the surface area of ​​the material will be too large, and the side reactions with the electrolyte will increase, resulting in a decrease in specific capacity and a decrease in the first effect. If the size of the graphite matrix is ​​too large, it will make it difficult for lithium ions to diffuse into the interior of the material, which will also lead to a decrease in specific capacity. In the first ball milling, the speed is too low, although the time is long, it will lead to inadequate ball milling, resulting in insufficient subsequent capacity. High speed, but short time, also cannot fully ball mill, and the capacity is not fully utilized. The second ball milling has a low speed and a long time, which has a certain impact on the uniformity of dispersion; high speed, but short time, there will also be certain dispersion uniformity problems, which will affect the full utilization of the material's specific capacity. Spraying temperature that is too low or too high will affect the size of the particle size. Too small or too large a particle size will have a similar impact to that of too small or too large a graphite matrix, and will affect the capacity.

[0121] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium aluminum alloy composite graphite negative electrode material, characterized in that: The lithium aluminum alloy composite graphite negative electrode material comprises a graphite core and a carbon layer coated on the outer surface of the graphite core, wherein the carbon layer comprises a carbonaceous matrix and lithium aluminum alloy particles dispersed in the carbonaceous matrix; The thickness of the carbon layer is 50nm-500nm.

2. The lithium aluminum alloy composite graphite negative electrode material according to claim 1, characterized in that: The lithium aluminum alloy particles are Li x Al, wherein x is 0.1 to 0.5, and the D50 of the lithium aluminum particles is 10 nm to 150 nm.

3. The lithium aluminum alloy composite graphite negative electrode material according to claim 1 or 2, characterized in that: The D50 of the graphite core is 5 μm to 40 μm, and the graphite core is selected from one or more of natural graphite, flake graphite and artificial graphite.

4. The lithium aluminum alloy composite graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The weight ratio of the graphite core, the carbonaceous matrix and the lithium aluminum alloy particles is (30-85): (3-20): (13-60).

5. A method for preparing the lithium aluminum alloy composite graphite negative electrode material according to any one of claims 1 to 4, characterized in that: include: Step S1, mixing an aluminum source with a first dispersant, and sequentially performing pre-dispersion and a first ball milling to obtain a first slurry; Step S2, adding a lithium source, a graphite core and a carbon source to the first slurry, and performing a second ball milling to obtain a second slurry; Step S3, drying and calcining the second slurry in sequence to obtain the lithium aluminum alloy composite graphite negative electrode material.

6. The method for preparing the lithium aluminum alloy composite graphite negative electrode material according to claim 5, characterized in that: In step S1, The stirring speed of the pre-dispersion is 20 Hz to 50 Hz, and the time is 10 min to 120 min; The first ball mill has a rotation speed of 500 r / min to 2500 r / min and a time of 4 h to 48 h.

7. The method for preparing the lithium aluminum alloy composite graphite negative electrode material according to claim 5 or 6, characterized in that: In step S2, the rotation speed of the second ball mill is 2000r / min to 6000r / min, and the time is 1h to 8h.

8. The method for preparing the lithium aluminum alloy composite graphite negative electrode material according to any one of claims 5 to 7, characterized in that: In step S3, The drying is spray drying, and the inlet temperature of the spray drying is 200°C to 400°C, and the outlet temperature is 80°C to 100°C; The calcination temperature is 600° C. to 700° C., and the calcination time is 2 h to 20 h.

9. The method for preparing the lithium aluminum alloy composite graphite negative electrode material according to any one of claims 5 to 8, characterized in that: The D50 of the aluminum source is 0.5 μm to 40 μm; Preferably, the aluminum source is selected from one or more of aluminum oxide, aluminum hydroxide and boehmite.

10. The method for preparing the lithium aluminum alloy composite graphite negative electrode material according to any one of claims 5 to 7, characterized in that: The carbon source is selected from one or more of citric acid, malic acid, glucose, sorbic acid, sucrose, polyacrylic acid, polyvinyl pyrrolidone, ascorbic acid, asphalt, tartaric acid, carboxymethyl cellulose, polyethylene, polypropylene, polystyrene, phenolic resin, urea-formaldehyde resin, melamine-formaldehyde resin, epoxy resin, unsaturated polyester resin, polyurethane and polyethylene glycol; and / or, The lithium source is selected from one or more of lithium oxalate, lithium nitrate, lithium carbonate, lithium acetate and lithium hydroxide monohydrate; and / or, The dispersant is selected from one or more of N,N-dimethylformamide, N-methylpyrrolidone, isopropanol, acetonitrile, water, ethanol, acetone, toluene, xylene, chloroform, acetic acid, tetrahydrofuran and dimethyl sulfoxide.

11. A negative electrode plate, comprising the lithium aluminum alloy composite graphite negative electrode material according to any one of claims 1 to 4.

12. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode plate is the negative electrode plate according to claim 11.

Citation Information

Patent Citations

  • Aluminum-carbon composite materials and their preparation methods, negative electrodes, secondary batteries and electrical equipment

    CN109671932B

  • Aluminum-containing negative electrode material, negative electrode plate and lithium ion secondary battery

    CN112563511A

  • A nano-aluminum anode material for lithium-ion batteries and its preparation method

    CN113241434B